Contagion Effects of the Global Financial Crisis in US and European Real Economy Sectors - Kenourgios, Dimitris; Dimitriou, Dimitrios (Panoeconomicus, 2014)
This paper empirically investigates the contagion effects of the Global Financial Crisis (2007-2009) from the financial sector to the real economy by examining nine sectors of US and developed European region. We provide a regional analysis by testing stock market contagion on the aggregate level and the sector level, on the global level and the domestic/regional level. Results show evidence of global contagion in US and developed European aggregate stock market indices and all US sector indices, implying the limited benefits of portfolio diversification. On the other hand, most of the European regional sectors seem to be immune to the adverse effects of the crisis. Finally, all non-financial sectors of both geographical areas seem to be unaffected by their domestic financial systems. These findings have important implications for policy makers, investors and international organizations.Key words: Global financial crisis, Financial contagion, Real economy sectors, USA, Europe.JEL: G15, F30.